[J. Rey]: How to Dine in Style: The Art of Entertaining, 1920 - Jaine, Tom (Petits Propos Culinaires, 2015)
[J. Rey]: How to Dine in Style: The Art of Entertaining, 1920: Bodleian Library, 2013: 160 pp., hardback, £12.99.